2013
DOI: 10.1002/ppul.22842
|View full text |Cite
|
Sign up to set email alerts
|

Increased asthma risk and impaired quality of life after bronchiolitis or pneumonia in infancy

Abstract: Hospitalization for bronchiolitis in infancy is associated with an increased risk of asthma, and an increased use of asthma medication in adulthood at the age of 28-31 years. Impaired respiratory health-related quality of life in adulthood as measured by the SGRQ is present after bronchiolitis and pneumonia in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(96 citation statements)
references
References 41 publications
3
91
0
1
Order By: Relevance
“…2,3,23,24 However, many prospective cohorts have demonstrated that early-childhood wheezers have an increased risk of suffering from asthma later in childhood, 15,16,[25][26][27][28][29] adolescence, 4,17,30,31 and even in adulthood. 2,3,23,24 However, many prospective cohorts have demonstrated that early-childhood wheezers have an increased risk of suffering from asthma later in childhood, 15,16,[25][26][27][28][29] adolescence, 4,17,30,31 and even in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,23,24 However, many prospective cohorts have demonstrated that early-childhood wheezers have an increased risk of suffering from asthma later in childhood, 15,16,[25][26][27][28][29] adolescence, 4,17,30,31 and even in adulthood. 2,3,23,24 However, many prospective cohorts have demonstrated that early-childhood wheezers have an increased risk of suffering from asthma later in childhood, 15,16,[25][26][27][28][29] adolescence, 4,17,30,31 and even in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Poor housing, with overcrowding, provides a potent milieu for repeated exposure and infection with viral respiratory pathogens. There is mounting evidence that this impact may be long lasting, with a higher risk of asthma and lower respiratory health‐related quality of life …”
Section: Discussionmentioning
confidence: 99%
“…Although prospective studies of virologically confirmed RSV infection followed to adult life are limited and the link between RSV and adult asthma remains obscure, longterm studies in Finland demonstrated an increase in asthma prevalence in adulthood after severe bronchiolitis in infancy (13). In a group of children younger than 2 years of age hospitalized for bronchiolitis or pneumonia in which RSV was detected in 40% of cases, 25% of children reported asthma at ages 4-6 years as compared with only 12-15% at ages 8-15, but prevalence of asthma rose to 30% at ages 18-20 and up to 35% at age 30 (14)(15)(16)(17)(18) . Similar results were reported by this research group when specifically considering subjects hospitalized with bronchiolitis caused by RSV; asthma risk was not elevated during the second decade of life, yet increased in the third decade (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…In the longest ongoing longitudinal study of young children hospitalized with LRI in the first 2 years of life, 40% of whom were infected with RSV, prevalence of asthma decreased from 25% at age 4.5-6 years to 12-15% at ages 8-15, only to increase again to 30% at age 18-20 and up to 35% at age 30 (14)(15)(16)(17)(18). There was no clear explanation for this trend but the authors noted that, surprisingly, adults with a history of LRI were more likely to smoke than control subjects (18).…”
mentioning
confidence: 99%